1995
DOI: 10.1099/13500872-141-4-863
|View full text |Cite
|
Sign up to set email alerts
|

Flavohaemoglobin HmpX: a new pathogenicity determinant in Erwinia chrysanthemi strain 3937

Abstract: In an HmpX-strain, the synthesis of pectate lyases, which are pathogenicity determinants in E. chrysanthemi, was reduced in conditions of low oxygen tension. Using gus fusion in hmpX, it was shown that hmpX transcription was induced in coculture with tobacco cells. A putative function for HmpX is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
61
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 35 publications
5
61
0
2
Order By: Relevance
“…Pseudomonas syringae pv tomato carrying the avirulence gene avrB were transformed with a pRK415 broad host vector (Keen et al, 1988) carrying the complete coding sequence of hmpX (Favey et al, 1995) under control of the Lac promoter, which is constitutively active in Pseudomonas. Detailed description of the construction of pRK415-hmpX and maintenance in Pseudomonas is not provided (M. Boccara, C. Mills, J. Zeier, C. Anzi, C. Lamb, R. Poole, and M. Delledonne, unpublished data).…”
Section: Growth Of Plant-pathogens and Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas syringae pv tomato carrying the avirulence gene avrB were transformed with a pRK415 broad host vector (Keen et al, 1988) carrying the complete coding sequence of hmpX (Favey et al, 1995) under control of the Lac promoter, which is constitutively active in Pseudomonas. Detailed description of the construction of pRK415-hmpX and maintenance in Pseudomonas is not provided (M. Boccara, C. Mills, J. Zeier, C. Anzi, C. Lamb, R. Poole, and M. Delledonne, unpublished data).…”
Section: Growth Of Plant-pathogens and Infectionmentioning
confidence: 99%
“…We then compared the defense responses of NOdeficient plants and wild-type Arabidopsis following challenge with avirulent P. syringae pv tomato (Pst) bacteria. Additionally, we employed avirulent Pst expressing the hmpX gene from Erwinia chrysanthemi [Pst(avr-hmpX)] (Favey et al, 1995) that encodes a highly similar NOD to lower NO levels specifically at the side of pathogen infection. We then challenged wild-type Arabidopsis and hmp-expressing Arabidopsis plants with Pst(avr-hmpX) to study the effect of NO removal at both the plant and the pathogen side.…”
mentioning
confidence: 99%
“…Examples include the FHP protein t Present address: Krebs Institute for Biomolecular Research, Department of Alcaligenes eutrophus (Probst et al, 1979;Cramm et al, 1994;Ermler et al, 1995), HmpX of Erwinia chrysanthemi (Favey et al, 1995), Hmp of Bacillus subtilis (LaCelle et al, 1996), and the haemoglobins of the yeasts Candida sp. (Oshino et al, 1973a, b;Iwaasa et al, 1992) and Saccharomyces cerevisiae (Zhu & Riggs, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In 1986, Wakabayashi and coauthors reported the presence of a bacterial hemoglobin (Vgb) in Vitreoscilla cells, challenging the view that the distribution of hemoglobin was restricted to eukaryotes (for a review, see reference 37). Other hemoglobins found in many bacteria are two-domain proteins (6,11,27,44). The N terminus contains the heme domain, whereas the C terminus contains a reductase domain with potential binding sites for flavin (flavin adenine dinucleotide) and NAD(P)H (9).…”
mentioning
confidence: 99%